Analisis Pengembangan Strategi Penanganan Gelandangan dan Pengemis oleh Dinas Sosial Pemuda dan Olahraga di Kota Semarang - Praharani, Mei; Maesaroh, Maesaroh; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
This research began of interest in the phenomenon of the homeless and beggars the disease being social in semarang city, namely the city which is one of the big cities in indonesia with bears as the provincial capital. Complex development has left a little problem, namely poverty. Homeless and beggars is one shortcut undertaken a group of the community to earn a living with ease on behalf of poverty. Of course the job is not justified , because in addition to disturb public order, get money from mercy can be called around idly. The number of them in Semarang City has also increased even though the government has made various efforts. The number of homeless in 2011 are 29 people, they became up to 151 people in 2012. Beggars has also increased from 117 people in 2011, later became 500 people in 2012. Then what needs to be researched is how the strategy of handling of the homeless and beggars in Semarang City? This study investigates about strategy of handling homeless and beggars in Semarang City, identify things that block and supporter of handling, as well as strategic values that can be used as recommendations to devise a strategy. The research is descriptive qualitative research that uses a method of strategic management to express strategic issues intensively, deep, and comprehensive. Through SWOT Analysis and Litmust Test as an instrument for measuring the environment strategic in the identification of the barrier and supporters, and get the strategy required in handling of the homeless and beggars in Semarang City. The result showed that in handling beggars and homeless are still experiencing a few problems such as the quantity and the quality of human lacking human resources, limited rehabilitation institution facilities, the weak regulations, and others. The strategy which suggested is to optimize the use of human resources and the orphanage of rehabilitation there, through the existing budget can be maximized to improve the quality of human resources and other facilities like the rehabilitation porch and coaching against Gepeng related of the ability and skill. In the handling of a social issue should boost the public participation through many media recently, either the print media or audio visual media.